Dopamine Health and Disease - Chandra Yenisetti, Sarat (IntechOpen, 2018)
The chemical basis of human emotions has been an exciting aspect in biology. The "feel-good chemical" dopamine (DA) is a hormone and also a neurotransmitter, which performs a critical role in reward and movement control in the brain. DA also performs multiple other functions outside the brain. Regulating unrelated critical biological functions makes this chemical a vital factor for sustaining life in both health and disease. Dopamine - Health and Disease is an endeavour with an objective to understand and appreciate the biological functions of DA in human wellbeing and its potential utility in biomedical research. This effort will supplement scientific and non-scientific communities in stimulating a critical understanding of the biological purpose of "ticklish" DA, which eventually supports the human relentless effort to reduce the burden of disease. As the most exciting molecule,dopamine directly impacts day-to-day life. Anyone who has an eye for health and disease-related concepts will find this book a good read.